Schoology-Based Flip Classroom to Improve the Quality of Civics Teaching and Learning - Yuliyatno, Yuliyatno; Alkhakim, Fahmi Insan (IKIP PGRI Bojonegoro, 2024)
The purpose of the research includes: 1) describing the steps for implementing flipped classroom learning schoology apps based on Civics teaching and learning; 2) identify the affects interest in learning and the quality of Civics learning. Research design used was classroom action research (CAR) involving 32 students in Civics & English subjects. Data collection techniques used were observation, interviews, pre- and post-tests, as well as questionnaires. The data analysis used is theme-analysis. The results of this research showed that: 1) there are several steps in implementing the flipped classroom learning model based on schoology apps, including pre-action, action, and post-action stages; 2) there are several effects emerges: the positive results resulting from implementing this learning model include increasing motivation, students' interest in learning and learning outcomes in Civics subjects. Further research on how Student responses to the implementation of the flipped classroom based on schoology apps are recommended for carried out to improve the application of this learning model.